Panchakarma Intervention in the Management of Multiple System Atrophy (AYUSHDHARA, 2024)
Multiple System Atrophy (MSA) is a Neurodegenerative condition presenting with motor abnormalities including akinesia, rigidity and postural instability along with either autonomic failure (OH or neurogenic bladder) or cerebellar syndrome. Early involvement of speech and gait, absence of rest tremors, poor response to levodopa helps to differentiate MSA from Parkinsonism. The condition is managed symptomatically and the condition progresses relentlessly to death 7-10 years after onset. There is no direct diagnostic correlation to MSA in Ayurveda, however, it can be comprehended within the spectrum of Avrutavata. Objectives- By considering MSA as Kaphavruta vyana, an attempt has been made to evaluate the efficiency of Panchakarma procedures in the conservative management of the disease. Method- A case of MSA presented with symptoms of slowness of activities, urinary incontinence, difficulty in standing and walking was managed with Dashmoola Kashaya Seka, Mustadi Yapana Basti as per Kala Basti schedule. Result- The patient was assessed based on Barthel index for dependency. Conclusion- Panchakarma procedures along with Ayurvedic oral medications are having encouraging results in improving quality of life of patients suffering from MSA.